Computational study of a novel combination of dual-absorber structured perovskite solar cell with theoretical efficiency of 36.37% - Vishnupriya, Gopinathan; Sathya, Pichandi (Frontiers in Energy Research, 2025)
This research explores an innovative dual-absorber solar cell design that incorporates MAGeI3 and CsSnI3 layers, aiming to achieve efficiency levels that exceed those of current single-junction solar cells. Simulations conducted with SCAPS-1D software identified optimal layer thicknesses for both materials, resulting in a maximum efficiency that significantly surpasses previously documented values for similar configurations. When considering defect densities, the optimized parameters revealed a strong open-circuit voltage, a high short-circuit current density, and an impressive fill factor, leading to a noteworthy overall efficiency even at certain defect levels. The enhanced performance of this dual-absorber design is attributed to the complementary bandgaps of the materials, which improve light absorption and charge carrier dynamics. Specifically, the smaller bandgap of CsSnI3 allows for more effective harvesting of lower-energy photons, and the higher bandgap of MAGeI3 helps in the absorption of higher-energy photons, while the dual-layer structure minimizes recombination losses. Further analyses of quantum efficiency and current-voltage characteristics support the architecture’s potential to approach theoretical efficiency limits. This study suggests that the proposed dual-absorber configuration holds considerable promise for advancing solar cell technology and warrants further experimental validation.